Impact of a Hands-on Pre-Clinical Neurosurgery Elective Course on Second-Year Medical Student Interest and Attitudes. (October 2020) - Sansosti, Alexandra A; Jacobs, Rachel C; Safonova, Aleksandra; Jani, Ronak H; Schumann, Jack; Friedlander, Robert M; Lunsford, L Dade; McDowell, Michael M; Sekula, Raymond F
Introduction: Medical student involvement opportunities and educational experiences with surgical residents during medical school have been shown to increase the chance of students deciding to specialize in surgical specialties. This study aims to determine the effect of a neurosurgery elective during the second preclinical year on student interest and opinion of neurosurgery. Methods: Thirty-nine students completed opinion-based surveys and factual knowledge quizzes during a neurosurgical elective course over 3 iterations, which included lecture and skills lab instruction. Pre- and post-course surveys used the Likert scale, with a score of 1 corresponding to the most negative opinion and a score of 10 corresponding to the most positive opinion, in order to measure various aspects including interest in neurological surgery, understanding of the field, and perception of female inclusion in the field. Weekly pre- and post-lecture quizzes assessed practical knowledge of neurosurgical topics. Results: A higher percentage of students rated neurosurgery highly as a career possibility (⩾8/10 interest level) post-course (58.6%) compared to pre-course (45.7%). Post-course, students reported a significantly increased mean understanding of neurosurgery on the Likert scale compared to pre-course (6.1 ± 1.7 vs 4.4 ± 2.0; P  = .001). Knowledge based-content assessment revealed a significant increase in overall correct answers after lectures (meanpre  = 3.85, meanpost  = 5.05, P  = .001). Inclusion of female instructors in the second and third iteration of the course resulted in a significant increase in students' perception of female inclusion in the field of neurosurgery (7.6 compared to 5.6, P  = .01). Conclusions: Early exposure to subspecialties may assist in making important career decisions. The implementation of this neurosurgical elective improved medical students' perception of the field and enhanced knowledge of the lectures and procedures. This study can be used as a framework for implementation of this curriculum at other institutions.